2011
DOI: 10.1002/chem.201002818
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Gas Adsorption and Separation Capacity through Ligand Functionalization of Microporous Metal–Organic Framework Structures

Abstract: Hydroxyl- and amino- functionalized [Zn(BDC)(TED)(0.5)]·2DMF·0.2H(2)O leads to two new structures, [Zn(BDC-OH)(TED)(0.5)]·1.5DMF·0.3H(2)O and [Zn(BDC-NH(2))(TED)(0.5)]·xDMF·yH(2)O (BDC=terephthalic acid, TED=triethylenediamine, BDC-OH=2-hydroxylterephthalic acid, BDC-NH(2)=2-aminoterephthalic acid). Single-crystal X-ray diffraction and powder X-ray diffraction studies confirmed that the structures of both functionalized compounds are very similar to that of their parent structure. Compound [Zn(BDC)(TED)(0.5)]·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
120
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 184 publications
(131 citation statements)
references
References 71 publications
11
120
0
Order By: Relevance
“…A higher heat of adsorption is usually indicative for stronger framework CO2 interactions [47]. Representative values are 20kJ/mol for [Zn(1,4-BDC)(TED)], 30 kJ/mol for HKUST-1, 47 kJ/mol for Mg-MOF-74, 63 kJ/mol for MIL-100-Cr and 96 kJ/mol for mmen-Cu-BTTri [48][49][50][51][52]. The heat of adsorption curve ( Figure 8) has a relative maximum at a quantity adsorbed of about 4 cm 3 /g STP with 27.7 kJ/mol.…”
Section: Resultsmentioning
confidence: 99%
“…A higher heat of adsorption is usually indicative for stronger framework CO2 interactions [47]. Representative values are 20kJ/mol for [Zn(1,4-BDC)(TED)], 30 kJ/mol for HKUST-1, 47 kJ/mol for Mg-MOF-74, 63 kJ/mol for MIL-100-Cr and 96 kJ/mol for mmen-Cu-BTTri [48][49][50][51][52]. The heat of adsorption curve ( Figure 8) has a relative maximum at a quantity adsorbed of about 4 cm 3 /g STP with 27.7 kJ/mol.…”
Section: Resultsmentioning
confidence: 99%
“…In general, functionalization of organic linkers is performed to increase the affinity of the resultant material towards CO 2 molecules and to improve CO 2 selectivity over other molecules [147]. This can be achieved through the tuning of a MOF's physical and chemical properties to design an ideal CO 2 adsorbent, which can make use of both physisorption and chemisorption for capture.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Some reports have appeared on the introduction of synthesis a series of functionalized MOFs containing the BDC-X ligand (X = -NH 2 , -OH, -CH 3 and -NO 2 ) [28][29][30][31][32]. For instance, Kim et al [33] have studied that NH 2 -MIL-125 showed a higher catalytic activity and significantly superior CO 2 adsorption capacity than MIL-125.…”
Section: Introductionmentioning
confidence: 96%